Do bank customers prefer profit sharing investment accounts? a proposed conceptual framework - Rosman, Romzie; Ya’u, Isah; Othman, Anwar Hasan Abdullah (SciTePress Digital Library, 2019)
The concept of sharing profit earned by Islamic banks with their investors is one of the distinguishing features that set Islamic banks apart from their conventional counterparts. The contract of mudarabah is used by Islamic banks to mobilise funds with the objective to share profit with the investors. Any financial losses incurred by the banks in the course of their financing or investment is to be borne entirely by the depositors, except in cases of negligence and breach of contract. Based on literature that investigated the factors effecting the adoption of Islamic banking and finance products, the factors differ based on countries. It is found that GCC countries showed that religious factor in terms of compliance with the provisions of Shariah by the Islamic banks is the most important factor that influences the selection of Islamic banking products in the GCC countries. However, in the MENA region, it could be observed that religious belief and compliance with Shariah by Islamic banks were not the major factors that influence customer’s choice of Islamic banks unlike in the GCC countries. Not only that, it is also found that the factors that influence the choice of Islamic banks amongst customers in Asia were not consistent. Whereas some studies show religious inclination as the most important factor in choosing Islamic banks by customers especially in some studies in Malaysia, other studies show that high profit and low-cost service as the most important selection criteria. Hence, the proposed conceptual framework that integrated both the Theory of Reasoned Action (TRA) and Theory of Planned Behaviour (TPB) together with the unique elements of religiosity and risk tolerance are expected to predict the behaviour of profit sharing investment account holders. By understanding the behaviour of investors in choosing profit sharing investment account, this study can assist the management of the Islamic banks to develop strategies to attract and retain the investments. Moreover, this study can assist regulators to ensure that the rights of this class of investors is protected by the Islamic banks.